In Vitro Free Radical Scavenging Activity of Leaves Extracts of Withania somnifera - Panchawat*, Sunita (Recent Research in Science and Technology, 2011)
Free radical scavenging activity of ethanolic and aqueous extracts of Withania somnifera leaf was studied by in-vitro DPPH and NBT method. Addition of ethanolic and aqueous extracts of Withania somnifera leaf was found to scavenge the free radicals generated by a,a-Diphenyl b-Picryl Hydrazyl (DPPH) at (IC50 1663mg/ml and 1455mg/ml) respectively and superoxide generated by photo reduction of riboflavin scavenged by Nitro-blue-tetrazolium (NBT) at (IC50 1597mg/ml and 1352 mg/ml) respectively. These results indicates that leaf of Withania somnifera possess antioxidant property in vitro. Free radical scavenging activity of ethanolic and aqueous extracts of Withania somnifera leaf can be attributed to the presence of flavanoids and tannins in the extracts.